Upgrading lignin bio-oil for oxygen-containing fuel production using Ni/MgO: Effect of the catalyst calcination temperature. (1st November 2019) - Li, Haowei; Ma, Hongwei; Zhao, Weijie; Li, Xuehui; Long, Jinxing
Graphical abstract: Highlights: Efficient strategy is provided for oxygen-containing fuel production from lignin oil. 98% guaiacol is converted with 97% cyclohexanol selectivity at 160 °C for 3 h. Calcination temperature of Ni/MgO has a significant effect on the catalytic activity. 15%Ni/MgO-850 can be reused for six consecutive runs without obvious activity loss. The technology is effective for upgrading of both light and heavy lignin bio-oil. Abstract: Biofuel production from renewable resources is becoming an increasingly attractive option given the depletion of fossil fuels and the environmental problems caused by the excessive use of unsustainable energy resources. In this study, an efficient approach is provided for high-quality oxygen-containing fuel production from renewable lignin bio-oil. The results demonstrate that the calcination temperature has a remarkable effect on the catalyst structure, surface Ni content and physico-chemical properties of the Ni/MgO material, all of which result in significantly different performances in the upgrading of lignin bio-oil. At 160 °C for 4 h and 3 MPa of hydrogen, a 98% lignin bio-oil model compound of guaiacol is converted with 97% cyclohexanol selectivity in the presence of 15% Ni/MgO-850. Furthermore, the optimized catalytic system is reusable and shows good catalytic performance in the upgrading of both light and heavy lignin bio-oils, indicating that it is a promising strategy for renewable lignocellulosic biomass valorization.